2020
DOI: 10.1017/s0007485320000358
|View full text |Cite
|
Sign up to set email alerts
|

Pest status, bio-ecology and management of the false codling moth,Thaumatotibia leucotreta(Meyrick) (Lepidoptera: Tortricidae) and its implication for international trade

Abstract: The false codling moth (FCM), Thaumatotibia leucotreta (Lepidoptera: Tortricidae) is an insect pest which represents an important threat to the production and marketing of a wide range of agricultural crops in the African-Caribbean-Pacific (ACP) countries. The FCM reduces not only the yield and quality of the crop but also as a quarantine insect pest, restricts the trade of susceptible agricultural produce on the international market. In addition, little research has been conducted in the ACP countries on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…To identify the potential for T. leucotreta to establish in Australia, the areas of potential species invasion considered both climatic habitat suitability and host range [ 9 , 18 ], as well as the pest’s ability to disperse across susceptible hosts [ 9 ]. Given that T. leucotreta is a polyphagous pest, its host range could be much wider than currently known.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the potential for T. leucotreta to establish in Australia, the areas of potential species invasion considered both climatic habitat suitability and host range [ 9 , 18 ], as well as the pest’s ability to disperse across susceptible hosts [ 9 ]. Given that T. leucotreta is a polyphagous pest, its host range could be much wider than currently known.…”
Section: Methodsmentioning
confidence: 99%
“…This could involve ongoing economic losses, impact on reputation, customer loyalty and even import licensing [ 15 ]. Thaumatotibia leucotreta is typically polyphagous and can cause feeding damage to over 107 host species and subspecies, both cultivated and wild [ 6 , 7 , 9 , 16 , 17 , 18 ]. Although T. leucotreta has low natural dispersal ability across the landscape, it is able to move long distances via human-mediated pathways [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all samples used in this study were obtained from interceptions at Dutch import locations. Consequently, there is a sampling bias towards countries that trade large volumes of commodities on which FCM is present with the Netherlands [50]; Eastern sub-Saharan countries are well-represented, whereas Western sub-Saharan countries were absent in our samples. Even though the current study does not represent FCM's complete distribution range, the diversity observed among the south-eastern Sub-Saharan samples is large enough to justify the determination of linkages between mitogenomic diversity and geographic origin or host on which the specimen was found.…”
Section: Strains Linked To Different Host Plantsmentioning
confidence: 99%
“…In Ghana, the binary insecticides acetamiprid 16 g L−1 + indoxacarb 30 g L−1 (Viper ® ) and lambda cyhalothrin 15 g L−1 + acetamiprid 20 g L−1 EC (Protocol ® ) gave a 100% protection to the chilli fruits against T. leucotreta , while dimethoate (400 g L−1) + cypermethrin (36 g L−1) (Cydim Super ® ) and maltodextrin (Eradicoat T GH ® ) offered 71.2 and 85.8% protection, respectively (Adom et al., 2020).…”
Section: Overview Of Available Measuresmentioning
confidence: 99%